Proverty Alleviation Models and Strategy in Moluccas - Katje Tupamahu, Maria; D Saleh, Ramla; N Ralahallo, Fransiska (International Journal of Psychosocial Rehabilitation, 2020)
In the past few years the existing data shows that economic development continues to improve. Some macroeconomic indicators show a continuous increase, especially economic growth which continues to be above the national average and inflation is under control. However, Maluku's GRDP per capita is still below the National average, which causes the poverty rate in Maluku to remain high.The purpose of this study was to see how much influence the macroeconomic variables have on the Ministry of Health in Maluku and prepare a policy plan in the form of a poverty alleviation strategy in Maluku.This study used an econometric model ofPanel Data Regression (Pooled Least Square) with the Fixed Effect Model scheme combined with SWOT Analysis as an additional analysis to answer the objectives of this study. The results of this study indicate that macroeconomic variables have a significant and negative influence on the poverty level of 0.21%, which means that an increase in economic growth will reduce poverty by 0.21% while the inflation variable has a positive and significant effect on poverty by 0.14%. Meanwhile, the SWOT Analysis produced several recommendations among others: Increased coordination with the central government, Increasing the role of the community and business world in poverty alleviation, Increasing accessibility and economic equality, Optimizing the Utilization of Village Funds.